Modern concrete materials : binders, additions and admixtures : proceedings of the international conference held at the University of Dundee, Scotland, UK on 8-10 September 1999 - Dhir, Ravindra K.; Dyer, Thomas D. (London : Thomas Telford, 1999)
09